AWAR – AWAR PLANTS (FICUS SEPTICA BURM) AS TRADITIONAL MEDICINES IN USADHA TARU PRAMANA'S LONTAR - Subagia, I Nyoman; Suta, I Made (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2022)
This study discusses the Awar-Awar Plant (Ficus Septica Burm) as Traditional Medicine in Usadha Taru Pramana Lontar. The method used is a quantitative approach with Gravimetry, Semimikrokjeldahl, and Soxhlet methods. The research results obtained include: Chemical Content and Benefits of the Awar-Awar Plant (Ficus Septica Burm), namely; (1), 2-Demethoxytylophorine (2), Isotylocrebine (3), Tylocrebine (4), Tylophorine (5), 10S,13aR-anofine N-oxide (6), Dehydrotylophorine (7), and Ficuseptine A (8), flavonoid content in the form of kaempferitrin (9) and genistin (10), (11) and coumarin compounds. Its benefits are as a remedy for skin diseases, appendicitis, overcoming ulcers, overcoming venomous snake bites and shortness of breath.